Efficacy of Topical Timolol as Primary Monotherapy in Cutaneous Facial Infantile Hemangiomas. Issue 6 (September 2016) - Ng, Zhi Yang; Kang, Gavin Chun-Wui; Chang, Chun-Shin; Por, Yong Chen
Abstract : Abstract: Recent studies have shown that infantile hemangiomas (IHs) undergo a rapid growth phase between 5.5 and 7.5 weeks of life and do not usually proliferate beyond 6 months; growth thereafter is usually proportionate to the child's growth. This review assesses the evidence for topical timolol as primary monotherapy for cutaneous facial IHs before 12 months of age, and to determine the differences in outcome between early (before 6 months) and late initiation (after 6 months) of timolol. A review of English language articles published up to November 2015 was performed using selected key words. Articles identified were further reviewed for relevance. The full text of studies included for final analysis was perused to include pertinent patient details, treatment protocol with timolol, complications (if any) reported, and response to treatment. Four studies met the inclusion criteria. In children before 12 months of age, the efficacy of topical timolol for the treatment of cutaneous facial IHs in achieving clinically significant improvement as defined by a standardized Global Assessment Score score of 3 and above ranged from 47% to 88%. One study also showed that IH regression was greater in patients started on timolol before 6 months of age compared with those started later ( P  <0.05). Topical timolol initiated in children before 12 months of age appears to be safe and clinically effective. There was insufficient data for detailed analysis of outcomes in patients who commenced treatment before and after 6 months of age.